Continuous treatment of high strength wastewaters using air-cathode microbial fuel cells. (December 2016) - Kim, Kyoung-Yeol; Yang, Wulin; Evans, Patrick J.; Logan, Bruce E.
Highlights: High strength wastewater was treated for 185 d in continuous flow mode MFCs. A maximum power density of 750 mW/m 2 was achieved after 12 d of operation. The power density decreased by 85% due to cathode fouling after 185 d. COD removal efficiency was improved by using higher current densities. COD removal rates were higher than those of low strength wastewaters. Abstract: Treatment of low strength wastewaters using microbial fuel cells (MFCs) has been effective at hydraulic retention times (HRTs) similar to aerobic processes, but treatment of high strength wastewaters can require longer HRTs. The use of two air-cathode MFCs hydraulically connected in series was examined to continuously treat high strength swine wastewater (7–8 g/L of chemical oxygen demand) at an HRT of 16.7 h. The maximum power density of 750 ± 70 mW/m 2 was produced after 12 days of operation. However, power decreased by 85% after 185 d of operation due to serious cathode fouling. COD removal was improved by using a lower external resistance, and COD removal rates were substantially higher than those previously reported for a low strength wastewater. However, removal rates were inconsistent with first order kinetics as the calculated rate constant was an order of magnitude lower than rate constant for the low strength wastewater.